Search the RA collection - Royal Academy of Arts (2006)
[Dt.:] Über die Website sind die Sammlungen der Royal Academy of Arts online zugänglich. Verschiedene Suchoption ermöglichen die Suche nach Kunstwerken, Büchern oder Archivalien sowie nach Personen. In der Rubrik "artist of the month" wird mit zahlreichen Abbildungen ein Künstler eingehend besprochen. - [Engl.:] The Royal Academy Collections include paintings, sculptures, drawings, prints, historic books, (i.e. published before 1921), archives, historic photographs and plaster casts. It is possible to search any of these categories or for more advanced searches visit Search all collections to search across all media, or narrow your search by choosing to search Works of art, Books or Archives. Alternatively you can browse by the Name A-Z.